The Role of Plain Radiography in Diagnosing Brodie's Abscess: Clinical Image - Ujjwal Prakash Khanal; Mitu Sadashankar; Siddhartha Bhandari (Clinical Case Reports)
ABSTRACT Plain radiographs can still be of considerable diagnostic value for recognizing Brodie's abscess, especially in resource constrained settings.